2012
DOI: 10.5455/jice.20120525123150
|View full text |Cite
|
Sign up to set email alerts
|

Use of Aqueous Extract of Corn Silk in the Treatment of Urinary Tract Infection

Abstract: Aim: Worldwide about 150 million people were diagnosed with UTI each year. The increasing incidence of antibiotic resistance among bacterial pathogens necessitates medicinal plants as an alternate therapy in the management of UTI. Corn silk has been widely used as a folk medicine in Iraq. The aim of this study is to evaluate the clinical advantages of using the aqueous extract of corn silk in Iraqi patients with UTI. Method: This study was carried out on 42 patients of both sexes with age of 29.91±10.57 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…The dried material was ground by using a grinder, and then stored in a drying cabinet at 4±1°C until used. Corn silk tea extract (CSTE) was prepared separately by putting 72 mg of corn silk powder in boiled water (60 ml) for 15 min as mentioned by Sahib et al (2012). This extract was prepared freshly every day and given three times a day in a dose of 5 ml / rat by using a stomach tube.…”
Section: Methods: Preparation Of Corn Silk Powder and Its Extractsmentioning
confidence: 99%
“…The dried material was ground by using a grinder, and then stored in a drying cabinet at 4±1°C until used. Corn silk tea extract (CSTE) was prepared separately by putting 72 mg of corn silk powder in boiled water (60 ml) for 15 min as mentioned by Sahib et al (2012). This extract was prepared freshly every day and given three times a day in a dose of 5 ml / rat by using a stomach tube.…”
Section: Methods: Preparation Of Corn Silk Powder and Its Extractsmentioning
confidence: 99%
“…Fresh corn (Zea mays) were obtained from the local markets in Kirkuk city, and corn silk was separated from the rest of the corn and washed with distilled water and dried, by using filter papers and incubated at 40ºC for 5 days, then powdered.Then powdered material was dissolved in organic solvents namely ethanol and chloroform, and using of Agar well-diffusion method (Nessa et al, 2012;Sahib et al, 2012;AL-kufaishi and Al-Mashhedy, 2012;Hilmi et al, 2014;Morshed and Islam, 2015;Haslina and Eva, 2017).…”
Section: The Collection and Preparation Of Corn Silk Extractionmentioning
confidence: 99%
“…It has been used against many pathogens and to treat urinary tract infections, as well as for treatment of high blood pressure and as a diuretic effect, and as previous researches suggested that it can be used to enhance immunity and treatment of bladder pain in people with urinary tract infection And to kill the germs causing itthrough the change of urines pH and not allowing the germs to adhesion to the cells (Sahib et al, 2012;Morshed and Islam 2015;Žilić et al, 2016;Haslina and Eva, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Eine klinische Untersuchung mit 42 eingeschlossenen Patienten mit UTI belegte eine signifikante Reduktion klinischer Symptome nach Anwendung wässriger Maisgriffelextrakte, verbunden mit einer Erythrozyten-und Leukozyten-Reduktion im Urin [12]. In-vitro-Untersuchungen zeigten antiinflammatorische Effekte eines hydroalkoholischen Maisgriffelextraktes, die auf eine verminderte Freisetzung von TNFα, einer verminderten bak teriellen LPS-induzierten Adhäsion von Monozyten an Endothelzellen und auf eine Hemmung interzellulärer Adhäsionsmoleküle (ICAM-1) zurückgeführt wurden [13].…”
Section: Positive Klinische Studieunclassified